Learn multiplication using gaming approach / Datu Muhammad Sophian Datu Arifin - Datu Arifin, Datu Muhammad Sophian (2006)
Computer games, a place that asks children to enjoy what they learn with a combination of many media by simply using a computer mouse to point and click on a particular picture, word, or button, and stories as well as information will come alive on a computer screen. The problem with today learning system is the students have to take a long time in memorizing multiplication table. The development of multimedia courseware needs suitable approaches to integrate various media effectively. This project is to develop a courseware on learning multiplication using gaming approach that target primary student ages between seven to twelve and applying. This courseware is based on mathematic syllabus from Kementerian Pendidikan Malaysia where it is applying; multiplication one to multiplication 12 and the courseware development based on /Mlesi and Trollip model. This project also educates the student to learn multiplication table in the easiest and fast ways. T}iis project is developed using Macromedia Flash 8 thai implementing rich multimedia. As conclusion, this project will benefits the educational field in the area of mathematics and improves learning multiplication.